(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
As clouds are now containering most of world data and guarantee its safety with a service level agreement, more and more organizations are shifting their data on cloud. The technological infrastructure provided by the client allows the application to maintain the historical data and pour continuously streaming transactional data. This data after some time joins the data ware house after the suitable treatment. The gross data piled up over time need to be analyzed or various purposes. This is where Big Data technologies come in the picture. Organization uses various mining techniques on this Big Data to get relevant findings. The question here is how secure your big data is and how it safeguards against an adversary which access the data either from the data store or on fly.. In this paper the confidentiality of data is protected by k-means approach off data mining using digital signature and homomorphic encryption for the data which is distributed across various containers.